The church in the British Isles; sketches of its continuous history from the earliest times to the restoration - Church Club of New York; New York Public Library (New York E. & J.B. Young & Co., 1893)
The Celtic church [by] W.C. Doane.--The Anglo-Saxon church [by] S. Hart.--The Norman period [by] A.V.G. Allen.--The reformation period [by] H.T. Kingdon.--The Puritan reaction [by] T.F. Gailor.
Lectures by W.C. Doane, S. Hart, A.V.G. Allen, H.T. Kingdon and T.F. Gailor
Keywords: Great Britain -- Church history; Church History